THE STATE LABOUR INSPECTORATE AS A MECHANISM FOR PROTECTING THE LABOUR RIGHTS OF EMPLOYEES: LEGAL FRAMEWORK AND PRACTICE IN THE REPUBLIC OF UZBEKISTAN (World Conference on Social Sciences, Law and Public Policy, 2026)
The article is devoted to the legal status and practical activity of the State Labour Inspectorate as the central institution for protecting the labour rights of employees in the Republic of Uzbekistan. The author considers the history of the establishment of the Inspectorate, its place within the structure of the Ministry of Employment and Poverty Reduction, its functions and powers, and the procedure for conducting inspections and examining the appeals of citizens. Special attention is paid to the digitalisation of the Inspectorate's activity and to the transition towards a preventive, risk-based model of labour inspection carried out in cooperation with the International Labour Organization. On the basis of the analysis of the legal framework and practice, the author identifies the problems that reduce the effectiveness of the Inspectorate and proposes measures for its further development. It is concluded that the strengthening of the State Labour Inspectorate is a key condition for the real protection of the labour rights of employees in Uzbekistan.
Keywords: State Labour Inspectorate, labour rights protection, labour inspection, Ministry of Employment and Poverty Reduction, Labour Code, risk-based supervision, digitalisation, ILO Convention No. 81, Republic of Uzbekistan.